2019
DOI: 10.1016/j.devcel.2019.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt5b Signaling Directs Outlying Nkx2.5+ Mesoderm into Pacemaker Cardiomyocytes

Abstract: Pacemaker cardiomyocytes that create the sinoatrial node are essential for the initiation and maintenance of proper heart rhythm. However, illuminating developmental cues that direct their differentiation has remained particularly challenging due to the unclear cellular origins of these specialized cardiomyocytes. By discovering the origins of pacemaker cardiomyocytes, we reveal an evolutionarily conserved Wnt signaling mechanism that coordinates gene regulatory changes directing mesoderm cell fate decisions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(104 citation statements)
references
References 75 publications
(173 reference statements)
5
97
1
Order By: Relevance
“…Our data demonstrate that peripheral VCS precursors of the PF network, like central VCS components, emerge from populations of cardiac progenitor cells that are specified but remain electrically inactive during the initial stages of heart tube development, as has been shown for pacemaker progenitor cells in avian embryos 33 . More recently Ren et al show that these latter specialized cardiomyocytes originate from outlying Nkx2.5+ mesodermal progenitors that downregulate Nkx2-5 prior to differentiation 35 . This study highlights the different requirements for Nkx2-5 expression during development of distinct regions of the conduction system.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that peripheral VCS precursors of the PF network, like central VCS components, emerge from populations of cardiac progenitor cells that are specified but remain electrically inactive during the initial stages of heart tube development, as has been shown for pacemaker progenitor cells in avian embryos 33 . More recently Ren et al show that these latter specialized cardiomyocytes originate from outlying Nkx2.5+ mesodermal progenitors that downregulate Nkx2-5 prior to differentiation 35 . This study highlights the different requirements for Nkx2-5 expression during development of distinct regions of the conduction system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent publications reported activation of WNT in similar differentiation timing to promote pacemaker-like CMs in hPSCs. While one recent publication reported that canonical WNT3a activation promotes pacemaker-like CMs from hPSCs, another reported a typically non-canonical WNT5b activation that regulates the planar cell polarity pathway is responsible for inducing pacemaker-like CMs from hiPSCs ( Liang et al, 2020 ; Ren et al, 2019 ). Based on the literature, the combination of NODAL inhibition by SB with canonical or non-canonical WNT activation in cardiac mesoderm on further improving the induction of pacemaker-like CMs from hiPSCs warrants additional studies.…”
Section: Discussionmentioning
confidence: 99%
“… Wnt5b activated a conserved canonical Wnt signaling pathway to guide the differentiation of Nkx2.5+ cardiac progenitors into primary pacemakers. [ 72 ] …”
Section: Frontier Of 3d Bioprinting In Cardiac Tissue Engineeringmentioning
confidence: 99%